The Association Between Venous Ulcer Area and Time to Healing Following Venous Ablation : A Comprehensive Systematic Review - Muchamad Zubaid; Kun Sriwibowo; Muhammad Zulbani (International Medical Journal Corp. Ltd, 2026)
Introduction: Venous leg ulcers (VLUs) affect millions worldwide with significant morbidity. While endovenous ablation addresses underlying venous reflux, the prognostic role of baseline ulcer size on healing time remains inadequately characterized. This systematic review synthesized evidence on the relationship between baseline venous ulcer area and time to healing following venous ablation. Methods: Seventy sources were systematically reviewed using predefined criteria: adult patients with venous ulcers undergoing ablation, reporting baseline ulcer size and healing time. Data extraction encompassed ulcer size parameters, healing time metrics, size-healing relationship analyses, and study characteristics. Results: Twenty-four studies reported baseline ulcer size, and 48 reported healing time. Measurement methods were heterogeneous: area (cm²) reported by Weber et al. (7.7±10.7 cm²), Sermsathanasawadi et al. (2.8±2.0 cm²), and Ivanova et al. (391.3±100.42 cm²); diameter categories used by Uttaray et al. (<2, 2-4, >4 cm) and Gohel et al. (<2, 2-6, >6 cm). Healing times ranged from 22 days for small ulcers (Savolyuk et al.) to median 56-82 days (EVRA trial). Savolyuk et al. demonstrated size-dependent healing: 7-21 cm² ulcers healed in 22.3±0.9 days versus 29.1±0.7 days for larger ulcers. Uttaray et al. observed non-healing associated with ulcers >5 cm. Tenbrook et al. identified diameter >2 cm as a non-healing risk factor. Discussion: Larger ulcers require greater tissue regeneration and are associated with longer disease duration and more severe dermal damage. Despite biological plausibility and recognition of size as a prognostic variable (stratification in VUERT and AAVTIRS trials), direct evidence remains limited. Studies primarily compared ablation modalities rather than examining size as a predictor. Heterogeneity in measurement methods and insufficient statistical power constrain definitive conclusions. Conclusion: Current evidence suggests larger venous ulcers heal more slowly following ablation, but the association lacks robust quantification. Future research requires standardized size measurement and adequate sample sizes for size-stratified analyses.